The Hypertensive Heart: An Integrated Understanding Informed by Imaging - Raman, Subha V. (2010)
Clinical sequelae of hypertension include heart failure, arrhythmias, and ischemic events, especially myocardial infarction and stroke. Recognizing the hypertensive heart has both diagnostic as well as prognostic implications. Current imaging techniques offer noninvasive approaches to detecting myocardial fibrosis, ischemia, hypertrophy, and disordered metabolism that form the substrate for hypertensive heart disease. In addition, recognition of aortopathy and atrial myopathy as contributors to myocardial disease warrant incorporation of aortic and atrial functional measurements into a comprehensive understanding of the hypertensive heart.